Enhancing Autonomy-Connectedness in Patients With Anxiety Disorders: A Pilot Randomized Controlled Trial - Maas, Joyce; van Balkom, Ton; van Assen, Marcel; Rutten, Liesbeth; Janssen, Daniella; van Mastrigt, Marietta; Bekker, Marrie (Frontiers in Psychiatry, 2019)
Autonomy-enhancing treatment (AET) is a person-centred, gender-sensitive treatment, targeting transdiagnostic personal autonomy deficits. The current study was set up as a first pilot RCT to investigate the preliminary efficacy of AET. Earlier small non-controlled plots showed AET to be feasible and acceptable. In the current study (Trial Code = 3513), patients receiving 15-session group-based AET (N = 43) were compared to a waitlist control condition (N = 40). Both the intention-to-treat and completers analyses suggested a larger decrease in agoraphobic symptoms in the experimental treatment than in the waitlist condition. In both analyses effect sizes were small. The completers analyses showed additional beneficial effects in two of three autonomy-connectedness components, as well as psychoneuroticism, anxiety, and depression, which disappeared after correcting for multiple testing. AET may alleviate agoraphobic symptoms in a patient sample with severe anxiety. Future research, including more stringent inclusion criteria and follow-up assessment, is needed to further evaluate whether AET may serve as a promising alternative or addition to existing approaches.